Analisis Dampak Nikah Muda terhadap Keadaan Mental Pasangan Suami Istri - Ummu Aiman; Leny Sri Wahyuni; Anisatun Muthi’ah; Mustofa Mustofa; Iksan Ghofur (Gunung Djati Conference Series, 2023)
This study aims to discuss the effect of young marriage on the mentality of the wife's partner. This research uses a qualitative approach by applying descriptive-analytical methods. The results and discussion in this study show based on the results obtained that Most married couples who marry at their young age feel no have freedom and the emergence of a sense of regret after marriage due to the lack of fulfillment of all needs, such as biological, psychological, social and economic needs. This study concluded that the influence of young marriage on the mental state of married couples is very sad, Because it often causes a lot of controversy in the household that makes the couple's mentality decline and traumatize in living a future life. therefore this study recommends Islamic institutions and organizations to pay more attention to or even prevent the occurrence of young marriages, considering the mental influence of married couples who have experienced it.